2017
DOI: 10.2215/cjn.02100217
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Randomized, Controlled Trial of Patient Navigators and Enhanced Personal Health Records in CKD

Abstract: We successfully developed a patient navigator program and an enhanced personal health record for the CKD population. However, there were no differences in eGFR decline and other outcomes among the study groups. Larger and long-term studies along with cost-effectiveness analyses are needed to evaluate the role of patient navigators and patient education through an enhanced personal health record in those with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…109 Another pragmatic trial evaluated patient navigator programs and enhanced personal health records for the empowerment of patients with CKD. 110 Novel interventions using real-time electronic health data and embedded metrics for CKD risk prediction models and education are also being tested for their ability to improve implementation of evidence-based practice. 111 Patient, policymaker, payer, and health system engagement in kidney disease epidemiology research Engagement of the consumer in research, including but not limited to patients, policymakers, payers, and health systems, is necessary to help align research directions with patient priorities and to enhance the impact of research outcomes on practice and policy.…”
Section: Epidemiology Studies To Enhance the Conduct Of Clinical Trialsmentioning
confidence: 99%
“…109 Another pragmatic trial evaluated patient navigator programs and enhanced personal health records for the empowerment of patients with CKD. 110 Novel interventions using real-time electronic health data and embedded metrics for CKD risk prediction models and education are also being tested for their ability to improve implementation of evidence-based practice. 111 Patient, policymaker, payer, and health system engagement in kidney disease epidemiology research Engagement of the consumer in research, including but not limited to patients, policymakers, payers, and health systems, is necessary to help align research directions with patient priorities and to enhance the impact of research outcomes on practice and policy.…”
Section: Epidemiology Studies To Enhance the Conduct Of Clinical Trialsmentioning
confidence: 99%
“…Despite the continuing high prevalence of lung cancer, there is a lack of effective approaches to assess symptoms in busy clinical settings. Studies have shown the increasing use of electronic personal health records to monitor disease progress (Fuji, Abbott, & Galt, 2015;Harrison et al, 2015;Navaneethan et al, 2017). However, such an approach has been argued to be physician oriented (Archer, Fevrier-Thomas, Lokker, McKibbon, & Straus, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…10 Registry implementation coupled with registry "navigators"-personnel with a background in health sciences but no advanced degrees in clinical medicine-is an approach to algorithmic medicine such as identification of abnormal eGFRs. 17 A navigator can perform the clerical tasks of entering an order for a follow-up eGFR test and alerting the provider of a CKD diagnosis. Registry navigators can also be used to perform tasks such as ensuring nephrology referral on behalf of PCPs, ensuring follow-up appointment scheduling, and facilitating transplantation appointment scheduling.…”
mentioning
confidence: 99%